The educational performance of immigrant children: Examination of the native-immigrant education gap - Fallesen, Helene Wind (Politica, 2017)
Why is there a native-immigrant education gap in Denmark? And has the gap been reduced over time? This article adds to existing research by examining the explanations behind the existence of the education gap and the development in the gap across time. The education gap is examined by comparing upper secondary completion rates for children graduating from compulsory school between 1990 and 2007. The education production function is estimated as a linear probability model with OLS. The article finds that the gap has narrowed significantly over the past 20 years and that differences in family background explain a large part of the gap. Furthermore, a strong relation between the child’s age at arrival and educational performance is found.